The Effect of Gamification and Price Discounts on Impulsive Buying Decisions Online on the Shopee Indonesia Mobile Application - Didi Tarmidi; Dikrikal Gumilang Setiawan (Enrichment : Journal of Management, 2022)
Due to the growing e-commerce industry in Indonesia, many e-commerce companies including Shopee are vying to increase their competitive power to acquire consumers and increase sales transactions, one of which is by using gamification strategies and discount prices. This research method uses a quantitative approach with survey instruments then described in descriptive analysis. The results showed that gamification and price discount strategies had a significant impact on Impulsivity Buying by 47.6%. Gamification strategies help direct consumer behavior patterns to spend more time using the Shopee application and to increase price discount sales conversions are given as game completion incentives to trigger impulse buying attitudes so that sales increase.